Evaluation of Staining Methods for Cytologic Diagnosis of Oral Lesions - Almeida, Janete Dias [UNESP]; Lima, Celina Faig; Brandão, Adriana Aigotti Haberbeck [UNESP]; Guimaraes Cabral, Luiz Antonio (Sci Printers & Publ Inc, 2008)
ObjectiveTo compare the efficacy of Papanicolaou, hematoxylin-eosin (H-E), Leishman and periodic acid-Schiff (PAS) staining for Cytologic diagnosis of oral lesions.Study DesignPatients from the Discipline of Stomatology, Sao Jose dos Campos Dental School, from the wards of Hospital Heliopolis and from the dentistry outpatient clinic of the University Hospital, University of São Paulo Medical School, with the following diseases, were selected: erythematous candidiasis (n = 9), pseudomembranous candidiasis (n = 10), squamous cell carcinoma In = 19), herpes simplex (n = 8), paracoccidioidomycosis In = 8) and pemphigus vulgaris (n = 1).ResultsThe different staining methods were compared regarding the quality of definition of cytoplasmic and nuclear morphologic characteristics and the identification of bacteria, fungi, inflammatory cells and secretions. Papanicolaou and H-E staining were considered better methods. In cases of fungal infections, PAS staining is useful and should be applied as a complementary method.ConclusionWithin the limitations of this study, it can be concluded that the cytologic diagnosis of oral lesions along with different staining methods is a useful tool for oral diagnosis. (Acta Cytol 2008;52:697-701)
Keywords: candidiasis, oral; carcinoma, squamous cell; cytology; diagnosis, oral; herpes simplex; paracoccidioidomycosis; pemphigus